Tailored versus conventional surgical debridement in complex facial lacerations in emergency department: A retrospective study. Issue 17 (28th April 2023) - Park, Byeong Kwon; Min, Jin Hong; Park, Jung Soo; You, Yeon Ho; Jeong, Won Joon; Cho, Yong Chul; Oh, Se Kwang; In, Yong Nam; Ahn, Hong Joon; Kang, Chang Shin; Kyung, Hyun woo; Kim, Joo Hak; et al.
Abstract : Surgical debridement is an essential step in treating complex facial lacerations (CFL). As the CFL severity increases, conventional surgical debridement (CSD) of wound edges becomes difficult and may be insufficient. Because the severity and shape of each CFL vary, it is necessary to tailor the customized pre-excisional design, that is, tailored surgical debridement (TSD), for each case before performing surgical debridement. The use of TSD can enable effective debridement of CFL with higher severity. This study aimed to compare the cosmetic outcomes and complication incidence of CSD versus TSD according to CFL severity. In this retrospective observational study, eligible patients with CFL who visited the emergency department between August 2020 and December 2021 were examined. CFL severity was graded as Grades I and II. The outcomes of CSD and TSD were compared using the scar cosmesis assessment and rating (SCAR) scale, wherein a good cosmetic outcome was defined as a SCAR score of ≤ 2. The percentage of good cosmetic outcomes between the 2 groups was compared. The SCAR score and percentage of good cosmetic outcomes between the 2 groups were compared overall and by severity. For analyzing complication incidence, asymmetry, infection, and dehiscence incidence were compared. In total, 252 patients were enrolled [121 (48.0%) CSD and 131 (52.0%) TSD]. The median SCAR scores were 3 (1–5) and 1 (0–2) in all enrolled patients ( P < .001), 2 (0–4), and 1 (0–1) in Grade I patients ( P < .01), and 5 (4–6) and 1 (1–2) in Grade II patients ( P < .001) in the CSD and TSD groups, respectively. The percentage of good cosmetic outcomes was 46.3% and 84.0% overall ( P < .001), 59.6% and 85.0% in Grade I patients ( P < .01), and 9.4% and 83.5% in Grade II patients ( P < .001) in the CSD and TSD groups, respectively. The incidence of complications was significantly higher in the CSD group than in the TSD group, but this was limited to asymmetry. No significant difference was noted in infection or dehiscence. Compared with CSD, TSD can lead to an objectively good cosmetic prognosis at higher CFL severity and can reduce facial asymmetry occurrence.